Comparative study of nyamplung (Callophylum inophyllum) kernel oil obtained from mechanical and chemical extraction for biofuel production - Hanifah Widiastuti; Meiti Pratiwi; Godlief F. Neonufa; Tatang H. Soerawidjaja; Tirto Prakoso (Jurnal Rekayasa Proses, 2019)
Nyamplung (Callophylum inophyllum) contains oil around 40-73% in its seed. It has recently gained recognition as a potential source for biofuel production. The oil recovery process from renewable sources such as nyamplung is widely carried out by using chemical extraction with solvents. Nevertheless, this method is considered costly and there are safety issues as well as environmental concerns related to the solvents used. Therefore, mechanical extraction has emerged as an alternative method. In this study, the nyamplung oil recovered by mechanical extraction via hydraulic press and chemical extraction utilizing Soxhlet extraction was compared. Soxhlet extraction was carried out by using n-hexane as a solvent with a temperature of 70 oC for 5 hours. Before the extraction process, the kernel was initially pretreated to reduce the particle sizes and the water content. The results show that the oil yield recovered using the hydraulic press is 58%, which is comparable with the value obtained from Soxhlet extraction (65%). The oil characteristics were also compared, and the profiling shows no significant difference in the properties (saponification value, acid value, and iodine value) of oils recovered using both methods. The composition of fatty acids was also analyzed for utilization as a biofuel feedstock. Higher content of oleic acid was observed in oil resulted from chemical extraction while mechanical extraction yielded oil with higher palmitic acid content.